A resilience analysis of the contraction of the accommodation and food service sector on the Scottish food industry - Revoredo-Giha, Cesar; Dogbe, Wisdom (Frontiers in Sustainable Food Systems, 2023)
The Scottish economy has been exposed to several adverse shocks over the past 5 years like the UK exiting the European Union (Brexit), the effects of the COVID-19 pandemic and the Russia-Ukraine war, which have resulted in disruptions of the food and drink supply chains. The purpose of this paper is threefold: to estimate (1) the degree of resilience of the Scottish food and drinks sector, (2) the effects on interconnected sectors of the economy; and (3) the economic losses which is the financial value associated with the reduction in output. This paper focuses on the impact that the sudden contraction that the ‘accommodation and food service activities’, resulting from the pandemic, had on the food and drink sectors. For this analysis, the study relied on the Dynamic Inoperability Input-Output Model (DIIM), which takes into account the relationships across the different sectors of the Scottish economy over time. The results indicated that the accommodation and food service sector was the most affect by the COVID-19 pandemic lockdown contracting by about 60 per cent. The DIIM showed that the disruption to this sector had cascading effect on the remaining 17 sectors of the economy. The Processed and preserved fish, fruits and vegetable sector is the least resilient whilst Preserved meat and meat products sector is the most resilient to final demand disruption in the accommodation and food service sector. The least economically affected sector was the other food products sector whilst the other services sector had the highest economic loss. Despite the fact that the soft drinks sector had a slow recovery rate, economic losses were lower compared to the agricultural, fishery and forestry sector. From the policy perspective, stakeholders in the accommodation and food service sector should re-examine the sector and develop capacity against future pandemics. In addition, it is important for economic sectors to collaborate either vertically or horizontally by sharing information and risk to reduce the burden of future disruptions. Finally, the most vulnerable sector of the economy i.e. other services sector should form a major part of government policy decision-making when planning against future pandemics.